Compressibility Characteristics of Compacted Snow - Abele, Gunars; Gow, Anthony J. (1976)
The effects of snow temperature and initial density on the stress vs density and stress vs deformation relationships were investigated for shallow compacted snow in the density range of 0.28 to 0.76 g/cu m, for stress range of 0.5 to 72 bars and a temperature range of -1 to -34 C at a deformation rate of 40 cm/s. A decrease in temperature increases the resistance to stress, the effect increasing with applied stress. For any stress, an increase in the initial density results in an increase in the resulting density, the effect decreasing with an increase in stress. The approximate yield envelopes, which define the stress required to initiate any deformation of snow of a particular density and temperature, were determined. Rapid compaction of snow results in extensive recrystallization, significantly different from that of naturally compacted snow. At a stress of 72 bars, transformation to ice occurs only at temperature above -10C.